PENGARUH PAPARAN BENZOPIRIN TERHADAP PENURUNAN RESPON IMUN HUMORAL MUKOSA ILEUM MENCIT Mus musculus L - Saikhu Ahmad Husein (The East Java Biological Society, 2000)
The influence of benzopyrene exposure on the decrease of humoral immune response in ileum of mice, was studied to demonstrate the reduction of immunocompetent cell components that may decrease mucosal immune response, especially decrease of active plasma cells in the ileum of mice exposure benzopyrene in different dose, exposure period, and combination of dose and exposure period. This study used 36 mice, which were divided into three dose group (0, 10, and 20 mg/kg BW). Each dose group was subdivided into 4 different period groups (1, 2, 4, and 8 weeks). In control group, olivarum oil was given orally to each mice, while in the treatment groups, benzopyrene solution of 10 mg/kg BW (P1) and 20 mg/kg BW (P2) as much as 0.2 ml was given orally to each mice during the determinant periods. Result showed that variables active plasma cells, period factor were not significantly different, while dose factor and combination of dose and period were significant different.